A STUDY OF OUTCOME OF ROSE K LENSES IN KERATOCONUS - A Chaudhary, Snehal; B Bhatt, Rupal; Chauhan, Amita; Pandya, Jaimin; Brahmakshatriya, Ishan; Bhatt, Nishit (International Journal of Clinical and Biomedical Research, 2017)
Background: Cornea is affected by several distinct disorders that produce marked thinning without significant inflammation. They are keratoconus, posterior keratoconus, pellucid marginal degeneration, and keratoglobus. keratoconus and posterior keratoconus produces central and inferior thinning with ectasia. Materials and Methods: All patients of keratoconus in age group 15 to 60 years at various stages of progression were included this was a prospective study, 20 Eyes of 15 patients of keratoconus in age group of 15 to 60 years at various stages of progression were included in the study. Visual acuity, slit lamp Biomicroscopy was done, corneal topography and Fundus examination was done by both direct and indirect ophthalmoscopy with full dilatation when possible. Results: Subjective score of pre rose k eyes when compared to post rose k lens eye was highly significant, which signifies that the same patient was highly satisfied after wearing rose k lens. Conclusion: Present study observed that, Rose K lenses improved patient’s overall quality of life in moderate and advance cases of keratoconus. KEYWORDS: Keratoconus; Pellucid marginal degeneration; Keratoglobus; rose k lenses.